2021
DOI: 10.3390/agronomy11030523
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Nutrition in a Novel Single-Nutrient Source Hydroponic Solution

Abstract: Hydroponic systems are efficient for studying plant nutrition. It is often desirable to adjust individual nutrients for unique species’ needs and/or to create multiple nutrient deficiencies within the same study. However, this is challenging to do with traditional solutions as nutrients are generally added as dual nutrient salts, such as when varying phosphorus (P) concentration also affects nitrogen concentration; potentially, the chemical form of the nutrient taken up when ammonium phosphate is the source fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…could be used for pH adjustment, but their potential toxicity and interactions with the nutrient solutions would need careful consideration and study. Overall, it would be ideal to have a solution where pH could be maintained easily within a small pH range without the addition of mineral nutrients [62]. Wang et al [63] found that a mixture of three (HNO 3 , H 3 PO 4, and H 2 SO 4 ) acids was much more effective than only single acid for maintaining an optimal solution pH of 5.5-6.5.…”
Section: Figure 1 the Availability Of Different Nutrients At The Different Ph Bands Is Indicated By The Width Of The White Barmentioning
confidence: 99%
“…could be used for pH adjustment, but their potential toxicity and interactions with the nutrient solutions would need careful consideration and study. Overall, it would be ideal to have a solution where pH could be maintained easily within a small pH range without the addition of mineral nutrients [62]. Wang et al [63] found that a mixture of three (HNO 3 , H 3 PO 4, and H 2 SO 4 ) acids was much more effective than only single acid for maintaining an optimal solution pH of 5.5-6.5.…”
Section: Figure 1 the Availability Of Different Nutrients At The Different Ph Bands Is Indicated By The Width Of The White Barmentioning
confidence: 99%